2018
DOI: 10.1111/nmo.13386
|View full text |Cite
|
Sign up to set email alerts
|

Chicago Classification normative metrics in a healthy Indian cohort for a 16‐channel water‐perfused high‐resolution esophageal manometry system

Abstract: This is the first report of normative data for the 16-channel water-perfused system in supine posture. It revealed lower IRP and DCI, necessitating modification of CC cutoffs for this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The rest of the sensors are 3-cm apart spanning the length of the esophagus. 14 The tracings were analyzed using Trace 1.3.3 software after obtaining a minimum of 10 valid swallows (5 mL water) in the supine position. The following parameters were recorded: lower esophageal sphincter pressure (LES), integrated relaxation pressure (IRP), distal contractile integral, and distal latency (DL).…”
Section: High-resolution Esophageal Manometrymentioning
confidence: 99%
“…The rest of the sensors are 3-cm apart spanning the length of the esophagus. 14 The tracings were analyzed using Trace 1.3.3 software after obtaining a minimum of 10 valid swallows (5 mL water) in the supine position. The following parameters were recorded: lower esophageal sphincter pressure (LES), integrated relaxation pressure (IRP), distal contractile integral, and distal latency (DL).…”
Section: High-resolution Esophageal Manometrymentioning
confidence: 99%
“…As we have aforementioned, racial background and BMI affect HRM parameters. Different studies performed in Asian population 19,20,30,43 and European population 12,13 have found consistently lower values for DCI 95th percentile compared to studies performed in United States, 14‐16 these findings are important since DCI 95th value is relevant for diagnosing hypercontractile esophageal disorders, and using higher cutoff values may cause an under‐diagnosis in Asian and European population. Demographic factors are intrinsic to the population studied and, as such, cannot be modified; therefore, it is important to take into account demographic factors and how these variables can alter HRM results when interpreting studies performed on different populations.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, like others (6,8,12,(18)(19)(20)(21)(22)(23) , normal values were defined, dependent on what parameter studied, by the 5th and/or 95th percentile obtained in a population of healthy volunteers. Keeping in mind that this statistical analysis of results can induce, depending on the parameter, to a false abnormal result, simply by chance (5% or 10%).…”
Section: Discussionmentioning
confidence: 98%